ILMU PENGETAHUAN BERPARADIGMA UNITY OF SCIENCE - Erlina Laily Nur Afifa; Anisa Syahla Fitriana; Nia Anggraini; Nashikin Nashikin (STIT Sunan Giri Bima, 2022)
Unity of science is the unification of human science, both in the ontological, epistemological, and axiological aspects of that knowledge, in one unified truth of essential knowledge, and monotheism as the main basis. As explained that science is knowledge collected by scientific methods, it is also explained that science is a systematic collection of knowledge that is built through experimentation and observation. In other words, science will only be realized if it is cultivated, built, and developed. Based on this explanation, this article aims to find out how to develop science based on Unity of Science. The method used in this study is a type of library research (library), in this study using library data as the object of study in the research, using books, articles as data sources. The results of the study concluded that Unity Of Science includes a matter that every existing science cannot stand alone. There is a connection between one science and another. Every science is multidimensional, where in writing and studying a branch of science requires the involvement and assistance of other auxiliary sciences. Research in this context is the basis for increasing scientific development. Research activity is an effort to formulate problems, ask these questions, by finding facts and providing correct interpretations.